APLIKASI MONITORING JALAN RUSAK KOTA BOGOR BERBASIS ANDROID MENGUNAKAN GEOTAGGING (STUDI KASUS: DINAS BINAMARGA KOTA BOGOR) - Al-Ikhsan, Safaruddin Hidayat; Eosina, Puspa; Pratama, Ilham Surya (Krea-TIF: Jurnal Teknik Informatika, 2015)
The road is a transportation infrastructure covers all sections of roads, the building complements, and accessories that are on the surface of the soil. Breakdown related to road infrastructure such as hollow road, bumpy roads, can cause disruption of the process of distributing goods and services may even pose a risk of accident. BinaMarga Office is a government agency that is specialized to plan and execute the function of supervision of roads and bridges. Problems occurred at the Bina Marga Office Bogor City concerns the problem condition report of the damage path.  One source of information monitoring damage to roads is partly obtained from the report of the community but some of the information report is less specific  and reporting process takes a long time. Based on explanation above required a system that could deliver information quickly and accurately. Along with the development of the technology of smartphone with features of camera and GPS (Global Position System) can be used to take photos and mark the  location of an object with a method of geotagging. This research was  conducted on the design and development of monitoring  application  of the road damaged city of Bogor. The design is done with the model ofObject Oriented Design (OOD) who use tools for Unified Modeling Language (UML),the implementation is carried out by making Android applications. The application    of    monitoring    the   wayAndroid-based Bogor damaged using Geotagging. So that the application can facilitate the service of Binamarga to know the location of damage to the road in the town of Bogor and can be an alternative solution for the process of reporting the damage to roads occurred.